PERBANDINGAN ANALISA FUNDAMENTAL DAN TEKNIKAL DALAM PERDAGANGAN MATA UANG USD/JPY SETELAH PERISTIWA NON FARM PAYROLL - Andrew Limanto Angka; Rony Joyo Negoro Octavianus; Daniel Prasetyo (Universitas Katolik Widya Karya Malang, 2020)
This research was conducted to analyze the comparison of theresults of the trading on the currency pair USD/JPY one hourafter Non Farm Payroll’s release time using fundamentalanalysis, Stochastic Oscillator technical analysis, ADXtechnical analysis, and combination of technical analysisduring the period January 2015 to November 2016. Samplingtechnique used was the comparative analysis put forward bythe Nazir (2005) where the purpose of the comparativeanalysis is to compare between the two groups in one or morevariables. The research results showed that fundamentalanalysis has the return (in pips) which is the highest amongthe four others analysis. In the technical category, StochasticOscillator technical analysis has the highest number (in pips)of return than ADX technical analysis as well as combinationof technical analysis.